Speech Behavior of British Politicians in Discussion of Brexit: Pragmatics, Gender and Communicative Dominance in Political Media Discourse - A. G. Monogarova; T. A. Shiryaeva; A. Yu. Bagiyan (Научный диалог)
The article deals with the study of male and female speech behavior of British parliamentarians in the discussion of Brexit problems by various mass media. It is emphasized that the need to study the gender specifics of the speech behavior of women and men politicians commenting on Brexit in order to attract public attention is due to the extreme importance of media discourse. It determines the “agenda” of both an individual and various social institutions of modern society, on the one hand, and growing research interest in gender discourse studies, on the other. It is shown that institutionalization and ritualization form the basis of the gender manifestation of each individual’s belonging to a particular gender, and the generation and use of discourse cannot be studied outside the gender factor. The novelty and purpose of the study is to identify and analyze the complex linguistic gender specificity of the speech behavior of British politicians in political media discourse. The results of the analysis of the morphological, semantic and stylistic specifics of the speech behavior of British parliamentarians, when discussing Brexit in political media discourse in accordance with the gender of politicians are presented. The influence of social and psychological factors on the choice of pragmacommunicative design of the discursive space of the addressee, as well as the correlation of gender, pragmalinguistic tools and the effect of communicative dominance, have been proved.